Music and Technologies. - Davismoon, Stephen (Cambridge Scholars Publishing, 2013)
Based on the conference held in Kaunas, Lithuania, 2011, Music and Technologies aims to augment discussion within the field of interdisciplinary music research developed currently at such important forums as the CIM and the ISMIR. The book consists of a collection of articles written by musicians and computer scientists, educators and mathematicians from all over the world. The main contemporary ideas in the field of music technologies are explored - estimating the process of automatic cognit ...